Ketahanan Mental Prajurit TNI AD dan Implikasinya Bagi Ketahanan Hankam di Wilayah Kota Yogyakarta (Studi di Korem 072/PMK) = Mental Resilience of TNI AD and Implication to Resilience of Defense and Security Aspect in Y - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Reformation that occurs in Indonesia has brought many transformation in every aspects includes the transformation in TNI AD institution. The early reformation which produce many criticism even showed the role of TNI AD in the new period age, has perceived by TNI AD by held a reformation of internal TNI. With a new paradigm, TNI AD tried to get its self-identity as civil army, fighter army and national army. The implication of many blasphemies that received by TNI in reformation era has influenced the mental resilience of TNI AD soldier, particularly who has a weak mental endurance. It shows by the increase of the violation both disciplinary and law. If it were uncontrolled, it will influence the personality of the soldier, institution of TNI AD and also the aspects of national defense. In this research, the population of the research is the member of TNI AD soldier who takes a duty in Korem 072/Pamungkas Yogyakarta, and this research uses descriptive-qualitative method by collecting data through study of literature, questionnaire, interview and observation. The result of the research shows the that increase of violation both in disciplinary and law by TNI soldier in this reformation era is contrary with the fact that happens to TNI-AD soldiers that take a duty in Korem 072/ Pamungkas Yogyakarta. Every year, there is a reduction of violation both in disciplinary and law. So generally it is concluded that reformation in Indonesia, which caused TNI AD to reformed it